AS REPRESENTAÇÕES SOCIAIS DAS ADOLESCENTES ACOLHIDAS, NA CASA SANTA LUIZA DE MARILLAC E ASSOCIAÇÃO DE PROMOÇÃO A MENINA (APAM), EM RELAÇÃO AO COTIDIANO ESCOLAR – PONTA GROSSA/PR - Somer, Diana Galone (2017)
Social representations (RS) arise from durable points of conflict within the representational structures of the culture itself, and its denial to specific groups within society. RS are not an aggregate of individual representations. The first is linked to the group, and contributes to the construction of a reality common to a social set, so they are produced and shared by members of social groups. Now, the representations are linked to the individual, the knowledge is more individualized is based on personal experiences. As a continuous task, the school is present in the daily life of the adolescent, and is the object of different representations. The contemporary school still produces and conducts its practices influenced by society. In this context, the research has the general objective "to understand what are the social representations that the adolescents hosted in 2016, in Casa Santa Luiza de Marillac and in the Association for the Promotion of Girls (APAM), have in relation to school daily life." Thus, it is of great relevance the understanding of the link between RS and the daily life of adolescents. As school daily life is complex, it involves the construction of a RS that is strongly linked to diversity and affectivity and is permeated by interpersonal and intergroup relations. However, this study does not refer to a "generic" or "common" adolescent, but a specific adolescent, who is in vulnerability and social risk, and an analysis of their socio-historical context is necessary. For this, it is also necessary to understand some aspects that involve the construction of the representations of otherness, specifically radical alterity studied by Jodelet (1998), who presents the double process of construction and social exclusion. This research is qualitative and was developed using the following methodological procedures: bibliographic-exploratory research; Focus Group (GF); Content analysis of thematic categories. The subjects who participated in the research were adolescents hosted by the two mentioned institutions, after accepting the project submitted to the Ethics Committee, the GF was developed. The GF occurred in two sessions in each institution, with a script of twelve questions to understand RS, in relation to the daily schooling of adolescents. Thus, this work is presented in three chapters: the first one is a bibliographical review of the main concepts addressed: the theory of social representations, alterity and radical alterity, everyday school, public school and reception. In the second chapter, the concepts of vulnerability and social risk and adolescence are dealt with in the socio-historical context. In addition, in this chapter the characterization of subjects and field of research, as well as the methods used (GF and content analysis of thematic categories) are carried out. Finally, in the third chapter the analysis and discussion of the data are presented detailing the categories found. After the transcription of the material collected and the use of content analysis of thematic categories, the following categories were obtained: relationships and social interactions in the school; adolescence; bullying; Everyday life at school and welcome; and family. It was observed that the adolescents received have difficulties adapting with the new spaces: the reception and new school environment. Also, it was verified that the relationships and interactions constituted in the school environment, have great influence in the daily life, as well as in the RS of the adolescents hosted by Marillac and APAM. Positive relationships, which give the feeling of belonging, are with friends and general service employees. While negative relationships and interactions are with some teachers, peers and pedagogues. The main difficulties encountered in the daily life of adolescents are bullying, stigma and radical alterity. It is concluded that all these elements found in relation to the representations and RS of the school daily life of adolescents hosted in Marillac and APAM influence in the construction of their identity.